Family Needs of Patients Admitted in The Intensive Care Unit: A Meta-Synthesis - Ismail, Suhartini; Lahati, Nurul Safira; Morales, Jeremy Godofredo (Jurnal Keperawatan Soedirman, 2024)
The life threats for patients admitted in the Intensive Care Unit (ICU) is higher compared to other care units. The magnitude of the life threats in the ICU not only causes anxiety for patients but also for other families. The family has crucial roles in supporting the patient's recovery, so the holistic needs of the patient's family also require to be considered. This meta-synthesis aimed to synthesize findings from qualitative studies that explored and described the needs of families while accompanying patients in the ICU. A systematic literature search from online databases was used to conduct a qualitative meta-synthesis, which was then evaluated using Critical Appraisal Skill Programme (CASP) checklist for Qualitative Study. Literature that fit the requirements was further analyzed. Three main themes that were fundamental for families were revealed including the need for information, the need for family involvement in patient care, and the need for visiting time for the family. Understanding the family as a unit brings benefits to the patient. It is essential to adapt professional practice strategies that involve families in the daily care of critical patients. Further research is required on how to carry out interventions that translate this knowledge into nursing care practices and actions.